A simple validated RP-HPLC method for quantification of sumatriptan succinate in bulk and pharmaceutical dosage form - Jampala Balaji; K.Aruna; N.V.S.Naidu (International Journal of Pharmacy and Analytical Research, 2015)
A simple reverse phase high performance liquid chromatography method developed for quantification of sumatriptan succinate in bulk and pharmaceutical dosage form. This method achieved by using isocratic elution with mixed phosphate buffer (pH: 6.8) and acetonitrile mobile phase at 70:30 ratio, Hypersil BDS C18 (150 X 4.6mm, 5µm) column at temperature 30ºC, flow rate 1.0mL/min and 228nm UV with PDA detector. This method validated as per ICH guidelines. This method was simple, specific, precise, linear, accurate, robust and ruggedness for analysis of sumatriptan succinate.